2017
DOI: 10.5897/ajb2016.15747
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic models and parameters estimation study of biomass and ethanol production from inulin by Pichia caribbica (KC977491)

Abstract: The growth kinetics and modeling of ethanol production from inulin by Pichia caribbica (KC977491) were studied in a batch system. Unstructured models were proposed using the logistic equation for growth, the Luedeking-Piret equation for ethanol production and modified Leudeking-Piret model for substrate consumption. Kinetic parameters (X 0 , μ m , m, n, p and q) were determined by nonlinear regression, using Levenberg-Marquart method implemented in a Mathcad program. Since the production of ethanol was associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
2
3
0
1
Order By: Relevance
“…This study confirmed that the Logistic equation for the growth and the Leudeking Piret kinetic model for substrate utilization were able to fit the experimental data, and the same result was obtained by Kara Ali et al [43] Where they used the logistic empirical kinetic model and Leudeking Piret model and they obtained good agreement with the experimental data.…”
Section: Estimated Regression Coefficients Of T and P And Analysis Of...supporting
confidence: 88%
“…This study confirmed that the Logistic equation for the growth and the Leudeking Piret kinetic model for substrate utilization were able to fit the experimental data, and the same result was obtained by Kara Ali et al [43] Where they used the logistic empirical kinetic model and Leudeking Piret model and they obtained good agreement with the experimental data.…”
Section: Estimated Regression Coefficients Of T and P And Analysis Of...supporting
confidence: 88%
“…For substrate consumption, the Monod and Luedeking-Piret models are the ones that exhibit a closer fit to the experimental data, the latter being the one that best fits if the values of R 2 , AIC, and RMSE are considered. The experimental data resemble data reported in previous studies, where the data predicted with the model were highly compatible with the experimental kinetics, with satisfactory R 2 and RSME 60,61 .…”
Section: Mathematical Modeling To Determine the Kineticssupporting
confidence: 86%
“…The kinetics of product formation was based on the application of three unstructured models: Luedeking-Piret 27 , which depends on the growth rate and the instantaneous concentration of biomass ( 5), the logistic equation 28 that describes the production of LA ( 6), and the simple production model 29 that represents the generation of a product to be estimated (7).…”
Section: Mathematical Models For La Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linear and nonlinear calibration methods were used to build a prediction model of POD information by hyperspectral data. The PLS analysis was generally used for linear calibrations, and the SVM method was investigated for nonlinear calibrations [24] . After six days, the 90 undamaged leaves were randomly selected as the calibration set for each variety, and the remaining 30 samples were taken as the prediction set for each variety.…”
Section: Spectral Data Analysismentioning
confidence: 99%